2019
DOI: 10.1016/j.nedt.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Adapting and validating the Hospital Survey on Patient Safety Culture (HSOPS) for nursing students (HSOPS-NS): A new measure of Patient Safety Climate

Abstract: Background: Patient Safety Culture and Patient Safety Climate (PSC) are different factors. PSC is the shared perception that is held within a hospital's area or unit at a specific moment in time. This measure is necessary for designing activities for promoting and improving safety. It must include the perception of all the agents involved, including future nurses throughout their patient safety education. Objectives: The aim was to adapt and validate a new version of the Hospital Survey on Patient Safety Cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Patient safety is a fundamental aspect leading to the depreciation of adverse events in healthcare systems. Interest in the issue is exponentially growing worldwide, mainly because it is a global problem that directly impacts patient care quality (1,2). The overall concept of patient safety emerges from the Institute of Medicine (IOM) definition, referring to the "prevention of patient harm" (3).…”
Section: Introductionmentioning
confidence: 99%
“…Patient safety is a fundamental aspect leading to the depreciation of adverse events in healthcare systems. Interest in the issue is exponentially growing worldwide, mainly because it is a global problem that directly impacts patient care quality (1,2). The overall concept of patient safety emerges from the Institute of Medicine (IOM) definition, referring to the "prevention of patient harm" (3).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire is similar to the one in this study, composed of 21 items and 5 dimensions, and had good psychometric properties. Recently, Ortiz de Elguea et al [ 41 ] adapted and validated the Hospital Survey on Patient Safety (HSOPS) questionnaire [ 42 ] using a sample of 654 Spanish nursing students; however, this questionnaire aims to measure the safety culture and not competencies about patient safety. The existence of these questionnaires provides an opportunity to progress in the search for a valid and reliable instrument that will allow evaluating the patient safety competencies of nursing students in Spain and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that most European studies examining the psychometric properties of the HSOPSC questionnaire, resulted in reliable and valid models with fewer than the 12 dimensions of the original US HSOPSC structure. 5,7,8,2832 Therefore, it is common for the original US HSOPSC 12-scales model to be adapted in order to incorporate each country’s relevant patient safety cultural aspects. Similarly to other studies, our results showed that the ‘Non-Punitive Response to Error’ scale (Scale 7) had a weak internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…35 To achieve this, several scientific instruments have been developed and evaluated, such as the Hospital Survey on Patient Safety Culture (HSOPSC). 58 In Greece, the recent economic recession and the dramatic Gross Domestic Product drop have led to reduced healthcare expenditure, shortages in healthcare professionals and medical supplies, immense patients’ shift towards public healthcare structures, thus jeopardizing the provision of quality care. In fact, 20% of Greeks claim to have experienced a medical error while using healthcare services.…”
Section: Introductionmentioning
confidence: 99%